The Role of Green HRM and Sustainability Orientation on Pro-Environmental Employees - Judijanto, Loso; Sono, Mohammad Gifari; Rosid, Muhammad Abdul; Darojat, Ilma; Hakim, Adi Lukman (Westscience Press, 2025)
This study investigates the role of Green Human Resource Management (Green HRM) practices and Sustainability Orientation in fostering pro-environmental behavior among employees in Indonesia. Using a quantitative approach, data were collected from 140 respondents through a structured Likert-scale questionnaire (1-5) and analyzed with Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results reveal that Green HRM and Sustainability Orientation significantly influence pro-environmental behaviors, with Sustainability Orientation demonstrating a stronger impact. The R-square value of 0.578 indicates that these variables collectively explain 57.8% of the variance in pro-environmental behavior. These findings underscore the importance of embedding sustainability into organizational culture and implementing structured Green HRM strategies to promote environmental responsibility in the workplace. Recommendations for practice and suggestions for future research are discussed.